2020
DOI: 10.1002/lary.28626
|View full text |Cite
|
Sign up to set email alerts
|

EAT‐10 Scores and Fiberoptic Endoscopic Evaluation of Swallowing in Head and Neck Cancer Patients

Abstract: Objective The purpose of this study was to determine the relationship between patient‐reported symptoms of oropharyngeal dysphagia (OD) using the Eating Assessment Tool (EAT)‐10 and the swallowing function using a standardized fiberoptic endoscopic evaluation of swallowing (FEES) protocol in head and neck cancer (HNC) patients with confirmed OD. Methods Fifty‐seven dysphagic HNC patients completed the EAT‐10 and a FEES. Two blinded clinicians scored the randomized FEES examinations. Exclusion criteria consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
2
15
0
5
Order By: Relevance
“…A significant correlation was found in our study between residue score and Arabic Pedi-EAT 10 total score. These results were similar to those reported by residue assessment by FEES but in the adult form of the questionnaire EAT 10 [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…A significant correlation was found in our study between residue score and Arabic Pedi-EAT 10 total score. These results were similar to those reported by residue assessment by FEES but in the adult form of the questionnaire EAT 10 [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…9,35 PROs are more sensitive and may be a better means of capturing a patient's perception of their function. [46][47][48][49] We utilized PROs only as a means to screen functions that did not undergo clinical assessment by a provider (i.e., pain, distress, fatigue, and hearing), in an effort to ensure all functions were screened while taking into consideration the time required to fill out multiple surveys. This resulted in no collection of patient-reported information on functions such as eating, taste, xerostomia, and communication.…”
Section: Discussionmentioning
confidence: 99%
“…To date it is unknown if abnormalities during specific parts of the swallow study correlate with certain patient reported signs and symptoms of dysphagia. Specifically, in the head and neck cancer population the EAT‐10 questionnaire is found to have an indicative value for the presence of postswallow pharyngeal residue on FEES, 4 however, this relationship cannot be extrapolated to the general dysphagic patient. Previous studies have found a complementary relationship between quality of life survey results and videofluoroscopic swallowing study (VFSS) performance among patients with head and neck malignancies.…”
Section: Introductionmentioning
confidence: 96%